2019
DOI: 10.1038/s41598-019-52305-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of parameters governing damage resistance of nematic liquid crystals for high-power or peak-intensity laser applications

Abstract: We investigate the damage resistance of saturated and unsaturated liquid crystals (LC’s) under a wide range of laser excitation conditions, including 1053-nm pulse durations between 600 fs and 1.5 ns and nanosecond pulse excitation at 351 nm and 532 nm. This study explores the relationship between the LC’s resistance to laser-induced breakdown (damage) and the electronic structure (π-electron delocalization) of the constituent molecules. The laser-induced damage threshold at all wavelengths and pulse durations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…Furthermore, it is found that LIDT for MLC2132 is nearly identical, while MLC2073 LIDT is 1.5 times higher. This is in good agreement with their bandgap energy ratio (Table I) and, following [19], it confirms that mixtures with higher bandgap present higher resistance to laser damage for single-shot exposure. Besides, MLC2132 has a more deterministic behavior than the two other mixtures, which is not understood at this stage.…”
Section: Laser Repetition Rate Influencesupporting
confidence: 88%
See 4 more Smart Citations
“…Furthermore, it is found that LIDT for MLC2132 is nearly identical, while MLC2073 LIDT is 1.5 times higher. This is in good agreement with their bandgap energy ratio (Table I) and, following [19], it confirms that mixtures with higher bandgap present higher resistance to laser damage for single-shot exposure. Besides, MLC2132 has a more deterministic behavior than the two other mixtures, which is not understood at this stage.…”
Section: Laser Repetition Rate Influencesupporting
confidence: 88%
“…We underline that our measurements nicely complete the study reported in [19], in which the minimum laser pulse duration was 600 fs. Values reported for E7, the common mixture to both studies, are in overall good agreement.…”
Section: Laser Repetition Rate Influencesupporting
confidence: 84%
See 3 more Smart Citations